2011
DOI: 10.3109/02699052.2011.613089
|View full text |Cite
|
Sign up to set email alerts
|

Participation outcomes for children with acquired brain injury: A narrative review

Abstract: The available literature indicates that children and adolescents with ABI are at risk for participation restrictions. Research on recovery trajectories in participation after ABI in children is lacking. Longitudinal studies using explicit participation measures and higher quality research methodologies (quantitative, qualitative and mixed methods) are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…Review 435 subscale or section) was explicitly used according to the study authors to measure participation, attendance, or involvement; 8,28,29 (2) the instrument used to assess participation was a quantitative measure that was clearly named and/or was accompanied by the original reference; (3) the instrument was used in a study with children diagnosed with ABI or CP; (4) the instrument was used in a study including children (age <19y); (5) the instrument was used in an article reporting on an empirical study; (6) the instrument was used in an article that was published in a peerreviewed journal.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Review 435 subscale or section) was explicitly used according to the study authors to measure participation, attendance, or involvement; 8,28,29 (2) the instrument used to assess participation was a quantitative measure that was clearly named and/or was accompanied by the original reference; (3) the instrument was used in a study with children diagnosed with ABI or CP; (4) the instrument was used in a study including children (age <19y); (5) the instrument was used in an article reporting on an empirical study; (6) the instrument was used in an article that was published in a peerreviewed journal.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…In addition, children with ABI and CP experience restricted participation across home, community, and school settings. [3][4][5][6][7][8][9] Over the last two decades, participation has received increasing attention as the ultimate outcome of rehabilitation. Participation is one of the key components of the International Classification of Functioning, Disability and Health (ICF).…”
mentioning
confidence: 99%
“…Studies of social adjustment reported poor self-esteem, loneliness, maladjustment, and social isolation, in the context of reduced emotional control and aggressive antisocial behavior (Andrews et al, 1998;Fletcher et al, 1990;Ganesalingam et al, 2011;Levin et al, 2009;Max et al, 1998;Yeates et al, 2010). These social difficulties are known to be associated with persisting psychological problems, reduced social participation, and reduced quality of life Cattelani et al, 1998;Van Tol et al, 2011). Studies of social cognition described impaired emotional recognition and social problem-solving as their most consistent findings (Hanten et al, 2008;Janusz et al, 2002;Tonks et al, 2001;Warshausky et al, 1997) Predictors Surprisingly few studies considered the impact of injury factors.…”
Section: Tbi and Social Outcomesmentioning
confidence: 99%
“…14 Similarly, restricted involvement and changes in the intensity and diversity of participation in activities, in the home, school and community environments have been seen up to four years post-injury. 2,[15][16][17][18] To date, few of these studies have focused on early outcomes, which may provide a base for understanding ''brain effects'' as distinct from problems that relate more so to longer-term adjustment and re-integration difficulties.…”
Section: Introductionmentioning
confidence: 99%